Polymeric Nanoparticles: Polymeric Nanoparticles with Neglectable Protein Corona (Small 18/2020). Issue 18 (7th May 2020) - Alberg, Irina; Kramer, Stefan; Schinnerer, Meike; Hu, Qizhi; Seidl, Christine; Leps, Christian; Drude, Natascha; Möckel, Diana; Rijcken, Cristianne; Lammers, Twan; Diken, Mustafa; Maskos, Michael; et al.
Abstract : Currently it is assumed that each nanoparticle rapidly adsorbs proteins when it enters the living organism. However, this is not a general property of all nanosized drug delivery systems. In article number 1907574, Stefan Tenzer, Matthias Barz, Rudolf Zentel, and co‐workers present three self‐assembled polymeric structures, which are effectively free of a protein corona and additionally show prolonged circulation profiles in vivo.